Penerapan Terapi Brain Gym Terhadap Masalah Gangguan Memori Pada Ny”S” - Ahmad Kholid Fauzi; Husnul khotimah; Fatilah (CV Edujavare Publishing, 2024)
Introduction: One of the major health problems among the elderly is cognitive decline. Disorders in cognitive function usually begin with memory decline or recall (forgetfulness). Cognitive function is the main capital for humans in carrying out their daily life activities. Brain gymnastics is a simple body movement exercise that is done to stimulate the left and right brain (lateral dementia), lighten or relax the front or back of the brain (focusing dementia), and stimulate the system related to feelings or emotions, namely the midbrain (limbic) and cerebrum (central dementia). Research Method: namely using experimental methods, interviews/anamnesis, physical examination and supporting examinations. Results: After the intervention was carried out for 3 days, there was an increase in cognitive function. Conclusion: Brain Gym can improve cognitive function in the elderly.